40 The Peduli Youth Program: Empowering Youth Learning, Outreach, and Capacity Building to Prevent Early Marriage - Salsabila, Anisa Putri; Putri, Bintan Hikmalia; Wijaya, Dimas Aruna; Maharani, Salsabiila May; Suwita, Ade; Hadnasari, Dini; Fadhilah, Afifah Husni; Raraswati, Dellya; Widodo, Ginanjar Wahyu; Affandy, Mahendra Yusuf Putra; Adiatara, Revanza Alzena; Pradikas, Allefan Syah Binta; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Early marriage, defined as a union in which at least one partner is under 18 years old, remains a serious issue in Indonesia, including in Wonosobo, Central Java. This practice often leads to school dropout, limited economic opportunities, and reproductive health risks. To address this problem, the PEDULI Youth Program was developed with three main pillars: education, socialization, and productivity training, focusing on self-control, reproductive health, and time management. The program was implemented at the PIK-R Kemiriombo Village from July to August 2025 in three stages. The preparation stage involved coordination with village officials and the development of learning materials. The implementation stage consisted of self-control education, reproductive health socialization, and time management training. Finally, the evaluation stage was carried out through discussions and Q&A sessions to assess participants’ understanding. The results showed an improvement in participants’ knowledge about self-control, the risks of early marriage, reproductive health, and time management skills. These findings highlight that holistic education can empower adolescents to make responsible decisions, delay marriage, and share knowledge with peers. Therefore, the PEDULI Youth Program has proven effective in preventing early marriage and promoting healthy, productive adolescent development.